Improving the performance assessment of innovation processes in the context of see management based on information support - Vishtak, Inna; Burennikova, Nataliia; Maidanevych, Leonid (Eastern-European Journal of Enterprise Technologies, 2026)
The innovation process effectiveness in the context of management based on information support has been investigated in this study. The task addressed relates to the lack of a coordinated scientific and methodological approach to measuring and assessing the effectiveness of an innovative process, taking into account the role of information support to making effective management decisions. The study’s results include the approach improved to assess the effectiveness of the innovation process by applying SEE management and a structural and logical model constructed to form an appropriate information support, which reflects the relationship between the components of effectiveness. A feature of this study is the construction of a structural-logical model to form information support for assessing the effectiveness of the innovation process and to build a performance matrix that reflects the relationships between indicators of the enterprise’s innovative activity. The proposed matrix is integrated into the management information system (MIS) and provides increased validity of management decisions. The practical significance of research results is the possibility of using the proposed approach in the management systems of innovative activities at enterprises to increase the efficiency of planning and assessing the effectiveness of innovative processes. The implementation of the proposed approach contributes to the coordination of strategic and operational goals of the enterprise’s development, increasing the adaptability of innovative activities and forming an information basis for making management decisions under the conditions of digitalization of the economy and orientation on the principles of sustainable development